Evaluation of different mustard varieties under northern Telangana zone: Evaluation of different mustard varieties under northern Telangana zone - P MADHUKAR RAO; D PADMAJA; P MADHUKAR; R UMA REDDY (Journal of Oilseeds Research, 2020)
A field experiment was conducted to identify suitable variety among 6 mustard varieties (NRCHB 101,RH 406, DRMRIJ 31, NRCDR 2, Black gold and Local variety ) in terms of growth characteristics, yield and its attributing components in a randomized block design (RBD) at Regional Agricultural Research Station (RARS), Jagtial, during rabi seasons of 2017-18 and 2018-19 respectively. The result of the experiment revealed that among six varieties Black gold variety (1474 kg/ha) recorded significantly superior yield over other varieties and it was on par with NRCHB 101 (1369 kg/ha).